Research on run-time overhead of RM and improvement - LUO Ding-ding; ZHAO Hai; SUN Pei-gang; ZHANG Xi-yuan; YIN Zhen-yu (Tongxin xuebao)
RM algorithm is a classic fixed priority real-time scheduling algorithm, but in most embedded real-time sys- tems, where the workload is composed of many tasks of high frequency and short execution time, the overheads from context-switches of real-time operating system will lead to a low resource utilization rate if RM algorithm is directly used. By studying the preemption relationship of the tasks scheduled by RM algorithm, a model of context-switches overheads is established with task attributes, based on which the run-time context-switches overheads of RM algorithm are reduced by optimizing the release time of the tasks in embedded real-time systems. Finally, the experimental results show the va- lidity of the proposed strategy.